Government Crisis Communication in Academic Perspective: A Bibliometric Study of Scientific Publications - Prastowo, FX Ari Agung; Hafiar, Hanny; Wada, Ibrahim; Khang, Nguyen Tan; Ratnasari, Eny (Dirasat: Human and Social Sciences, 2026)
Objectives: This study reviewed and examined various aspects of government crisis communication, emphasizing several subject areas, including crisis communication, risk management, and social media influence. Methods: The study used bibliometric analysis to examine the trends and patterns of publications in government crisis communication. A comprehensive analysis of general information on government crisis communication, most productive countries, most popular scholarly sources, most productive affiliations, funding sources, most influential authors, and frequently occurring keywords revealed that “crisis communication” was the dominant issue. Other frequently occurring keywords were “COVID-19,” “risk communication,” “trust,” and “social media.” Results: The study highlighted the importance of government communication and the role of digital channels such as Twitter in disseminating information during a crisis. Leading institutions, including the University of Maryland and Nanyang Technological University, and leading scholars participated in the study. However, there are certain limitations; industrialized countries predominantly influence research and social media. Conclusions: Recommendations include formulating new ideas on crisis communication, researching non-digital media, and enhancing regional coverage. This research provides broader insights into how crisis communication strategies and their relevance to future crisis communication management continue to change and become increasingly complex.